Development of a yz scan system for the improvement of an automatic system of radioactive seed implants in prostate brachytherapy - Leonardo Santiago Melgaço Silva (Brazilian Journal of Radiation Sciences)
Brachytherapy is the use of radiotherapy with insertion of radiation sources close to the site that needs treatment. It has become an extremely sought-after option by research fields for its impressive efficiency and practicality. In addition to being a fast-paced procedure, it allows patients to leave hospital care very soon after it is done, without pain or with minor discomfort, which can be considered an advantage.